Kerjasama Ekonomi Singapura-Malaysia di Johor dan Dampaknya terhadap Kawasan Ekonomi Khusus Batam - Azrul Asyikin; Setiawan, Azhari (UIN ALAUDDIN MAKASSAR, 2025)
This study analyzes the potential impact of the Johor-Singapore Special Economic Zone (JSSEZ) on the development and competitiveness of Special Economic Zones (SEZs) in Batam. Initiated through a high-level agreement between Malaysia and Singapore, the JSSEZ represents a strategic advancement in regional economic cooperation, aiming to integrate complementary strengths such as land and labor in Johor with Singapore’s financial and technological capital. This paper adopts a systematic literature review method to compare the design, sectoral focus, and investment incentives of JSSEZ with existing SEZs in Batam. The study finds significant overlap in priority sectors, such as electronics manufacturing, digital economy, and logistics, which raises both competitive risks and collaborative opportunities. The analysis highlights that while Batam benefits from geographic proximity to Singapore and a long-established industrial base, it faces challenges in infrastructure, regulatory efficiency, and skilled labor retention. The paper argues that JSSEZ could either intensify competition or open up new synergies depending on policy responses and investment strategies. The study concludes that proactive alignment and regional coordination could transform the perceived competition into a mutually beneficial economic corridor.